2021
DOI: 10.1080/02656736.2021.1900926
|View full text |Cite
|
Sign up to set email alerts
|

US-guided high-intensity focused ultrasound (HIFU) of abdominal tumors: outcome, early ablation-related laboratory changes and inflammatory reaction. A single-center experience from Germany

Abstract: Marinova (2021) US-guided high-intensity focused ultrasound (HIFU) of abdominal tumors: outcome, early ablation-related laboratory changes and inflammatory reaction. A single-center experience from Germany,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The system consisted of a treatment table with an integrated high power focused US-therapy transducer (diameter 20 cm, focal length 15 cm, frequency 0.8 MHz), Significant reduction in tumour volumes of patients were seen from 6 weeks to 12 months after thermal ablation, as was acute induction of inflammation, including an increase in leukocytes 2, 5 and 20 h after thermal ablation, compared to baseline. Furthermore, non-statistically significant increases in IL-6 compared to baseline were seen 20 h after ablation (parameters: Treatment time = 124 ± 46 min, Sonication time = 932 ± 374 s, Energy = 343.9 ± 156.2 kJ, Power = 366 ± 91 W, Energy/Volume = 12.8 ± 4.5 kJ/mL) [203]. In a case study of a 48-year-old patient with unresectable metastatic pancreatic cancer, they were given "thermal" HIFU with the JC HIFU system as a palliative therapy after poor response to gemcitabine/erlotinib and subsequently to FOLFOX (folinic acid, oxaliplatin and 5-FU).…”
Section: The Immunological Effects Of Therapeutic Focused Ultrasound ...mentioning
confidence: 94%
“…The system consisted of a treatment table with an integrated high power focused US-therapy transducer (diameter 20 cm, focal length 15 cm, frequency 0.8 MHz), Significant reduction in tumour volumes of patients were seen from 6 weeks to 12 months after thermal ablation, as was acute induction of inflammation, including an increase in leukocytes 2, 5 and 20 h after thermal ablation, compared to baseline. Furthermore, non-statistically significant increases in IL-6 compared to baseline were seen 20 h after ablation (parameters: Treatment time = 124 ± 46 min, Sonication time = 932 ± 374 s, Energy = 343.9 ± 156.2 kJ, Power = 366 ± 91 W, Energy/Volume = 12.8 ± 4.5 kJ/mL) [203]. In a case study of a 48-year-old patient with unresectable metastatic pancreatic cancer, they were given "thermal" HIFU with the JC HIFU system as a palliative therapy after poor response to gemcitabine/erlotinib and subsequently to FOLFOX (folinic acid, oxaliplatin and 5-FU).…”
Section: The Immunological Effects Of Therapeutic Focused Ultrasound ...mentioning
confidence: 94%
“…After HE and immunohistochemical analysis of axillary lymph nodes, HIFU was observed to stimulate the immune responses of the whole body and significantly increase the number of effector T cells, activated CTLs, and NK cells. [124] Although many benign tumors can be treated with HIFU, [123] the coagulation necrosis caused by thermal effect is unsatisfactory in inducing immune responses. [125][126][127] To address it, combined therapy with other treatment methods is highlighted to magnify ablation outcomes for potentiating the immune responses after HIFU treatment.…”
Section: Nanobiotechnology-enhanced Hifu Ablation For Activating Immu...mentioning
confidence: 99%
“…Although many benign tumors can be treated with HIFU, [ 123 ] the coagulation necrosis caused by thermal effect is unsatisfactory in inducing immune responses. [ 125 , 126 , 127 ] To address it, combined therapy with other treatment methods is highlighted to magnify ablation outcomes for potentiating the immune responses after HIFU treatment.…”
Section: Clinical Physiotherapy‐activated or Combined Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In the pancreas, an early study using thermal ablation reported modulation of the immune response [ 103 ]. More recently, a retrospective study also reported immunomodulation and reduced tumor volume after a one-year follow-up subsequently to HIFU thermal ablation [ 110 ]. More anecdotally, two case studies reported abscopal effects following thermal ablation [ 111 , 112 ].…”
Section: Immunotherapymentioning
confidence: 99%